Aluminum recovery from multimaterial Tetra-Pak waste pyrolysis = Odzysk aluminium z produktów pirolizy odpadów opakowań Tetra-Pak - Klejnowska, Katarzyna; Lewandowski, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A constant growth of the multimaterial waste production can be observed in the recent years. The multimaterial waste that contain aluminum are especially hard to process due to the fact that multiple layers of various materials are bonded permanently. Tetra-Pak waste contain high amounts of paper (approx. 70%) and are usually processed in papermills in order to recover cellulose.
Keywords: pyrolysis; Tetra Pak; aluminum recovery; piroliza; odzysk aluminium